Elastic constants of non-modulated Ni-Mn-Ga martensite. (15th July 2017) - Sedlák, Petr; Seiner, Hanuš; Bodnárová, Lucie; Heczko, Oleg; Landa, Michal
Abstract: Room temperature elastic constants of non-modulated (NM) tetragonal martensite of a Mn-rich Ni-Mn-Ga alloy were determined by ultrasonic methods. The results are in good qualitative agreement with ab-initio predictions and confirm that NM martensite exhibits strong elastic anisotropy with shear instability related to the soft acoustic phonons mediating the reverse transition. The geometric arrangement of the softest shearing modes is shown to be identical as for the stress-induced fct martensite of the Fe-31.2 at.%Pd alloy. However, it markedly differs from the arrangement of the soft shearing modes in parent Ni-Mn-Ga austenite phase. Graphical abstract: